Qualificação da atividade inibitória da cafeína sobre motilidade e formação de biofilme em Pseudomonas aeruginosa - Gouveia, Clovis Queiroz (2022)
Pseudomonas aeruginosa is considered an opportunistic microbe, resistant to several drugs, and presenting some characteristics such as: Gram-negative, non-fermenting, aerobic rod, and WHO (World Health Organization) classified it as a critical pathogen listed among 12 priority bacteria. P. aeruginosa can form biofilms, i.e., agglomerates of microorganisms, found in monolayers or multilayers, enabling the formation of a polymeric extracellular matrix (MEP). Caffeine is a substance extracted from coffee and other plants and exhibits antimicrobial activity against Gram-negative and Gram-positive bacteria. The present study aimed to evaluate the effect of caffeine on some virulence factors in two specimens of P. aeruginosa, isolate TGC04 and strain ATCC 9027 (cells in planktonic form, biofilm formation on two surfaces, and on motility (swimming, swarming, and twitching). Caffeine at 1024 μL/mL moderately inhibited biofilm formation on plastic surfaces (between 46.9% and 65%), while on the vitreous surface, there was a weakly inhibition (26.8 %), with no activity to isolate TGC04. Motility assays used caffeine at 2064 μL/mL which exhibited inhibition greater than 1 cm in swarming and twitching, with no activity in swimming, compared to the control test.